Enantioselective catalytic synthesis of α-aryl-α-SCF3-β2, 2-amino acids. Issue 3 (9th January 2020) - Eitzinger, Andreas; Brière, Jean-François; Cahard, Dominique; Waser, Mario
Abstract : Novel α-trifluoromethylthiolated-β 2, 2 -amino acids were obtained in high enantiopurities under chiral phase-transfer catalysis. Abstract : We herein report a novel entry towards chiral α-SCF3 -β 2, 2 -amino acids by carrying out the ammonium salt-catalyzed α-trifluoromethylthiolation of isoxazolidin-5-ones. This approach allowed for high enantioselectivities and high yields and the obtained heterocycles proved to be versatile platforms to access other targets of potential interest.